TOTAL ANTHOCYANIN CONTENT AND ANTIOXIDANT ACTIVITIES OF PIGMENTED BLACK RICE (ORYZA SATIVA L. JAPONICA) SUBJECTED TO SOAKING AND BOILING (Jurnal Teknologi (Sciences & Engineering), 2018)
Pigmented rice contains high value of anthocyanin and antioxidant activity. However, the different process for black rice might affect the concentration of these phytochemicals. Therefore, the present study focused on the effect of soaking and cooking on the total anthocyanin content and antioxidant activity of pigmented black rice. The raw black rice was subjected to two treatments. First, black rice was soaked for 3 hours. Second, black rice was soaked and cooked for 15, 25 and 35 minutes. The study revealed that the second treatment (soaking and cooking) caused a significant (p<0.05) decreased in antioxidant activities and total anthocyanin content as compared to soaking. Highest losses in total anthocyanin and antioxidant activity in cooked black rice were as follows: 35 minutes > 25 min >15 min cooking. Î²- Carotene degradation rate was also highest in 35 minutes cooked black rice.